2007
DOI: 10.1037/0278-6133.26.3.361
|View full text |Cite
|
Sign up to set email alerts
|

Joint effect of dopaminergic genes on likelihood of smoking following treatment with bupropion SR.

Abstract: Although these results are suggestive, a more compelling test is needed of the hypothesis that dopaminergic gene interaction underlies, in part, the likelihood of smoking following treatment with bupropion SR. Most likely this will come from larger studies involving prospective randomization to treatment based on genotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 51 publications
1
32
0
Order By: Relevance
“…These results are consistent with more recent trials that have also shown that persons with A1/A1 or A1/A2 genotypes have more favorable response to NRT patch (Breitling et al, 2011;Stapleton, Sutherland, O'Gara, Spirling, & Ball, 2011). Others have suggested a gene (ANKK1) × sex interaction (E. C. Yudkin et al, 2003) or gene (ANKK1) × gene (CYP2B6 or SLC6A3) interactions Lerman et al, 2003;Swan et al, 2007), but the limited state of the science in 2006 precluded these details from informing the design of the current pilot trial, which is aimed at understanding the psychological and behavioral impact of the GF as opposed to the efficacy of the genetically tailored treatment.…”
Section: Introductionsupporting
confidence: 80%
“…These results are consistent with more recent trials that have also shown that persons with A1/A1 or A1/A2 genotypes have more favorable response to NRT patch (Breitling et al, 2011;Stapleton, Sutherland, O'Gara, Spirling, & Ball, 2011). Others have suggested a gene (ANKK1) × sex interaction (E. C. Yudkin et al, 2003) or gene (ANKK1) × gene (CYP2B6 or SLC6A3) interactions Lerman et al, 2003;Swan et al, 2007), but the limited state of the science in 2006 precluded these details from informing the design of the current pilot trial, which is aimed at understanding the psychological and behavioral impact of the GF as opposed to the efficacy of the genetically tailored treatment.…”
Section: Introductionsupporting
confidence: 80%
“…Most research on the role of genetic variation on smoking cessation pharmacotherapy has been directed to the two most widely accepted and licensed forms of smoking cessation therapy: nicotine replacement therapy (NRT) [111,[124][125][126][127][128][129][130][131][132][133][134][135][136][137][138][139][140] and the antidepressant bupropion (Zyban1) [129,137,[141][142][143][144][145][146][147][148][149].…”
Section: Influence Of Genetic Variations On Smoking Cessation Treatmentmentioning
confidence: 99%
“…First, genotypes associated with increased dopamine availability (increased or normal dopamine receptor availability or function, low dopamine transporter levels and low dopamine metabolism) predict a better response to bupropion [129,137,[142][143][144][145][146][147]149].…”
Section: Influence Of Genetic Variations On Smoking Cessation Treatmentmentioning
confidence: 99%
“…Recently, our group published a genome-wide association study of smoking cessation that disclosed an association between the relative efficacy of bupropion versus NRT for a cluster of SNPs that overlap with nicotine dependence SNPs in the NCAM1 gene region analyzed by Gelernter and colleagues (2006) (David & Munafo, 2008;Uhl et al, 2008). These overlapping associations of SNPs in the NCAM1/TTC12/ANKK1/DRD2 gene cluster and smoking cessation associations with NCAM1 SNPs are intriguing because multiple pharmacogenetic clinical trial investigations have found consistent associations between SNPs within the neighboring ANKK1 (i.e., rs1800497 "DRD2-TaqIA") and DRD2 (i.e., rs6277 "exon [S] C957T"; rs1799732 "promoter [-141 ins/del]") genes and efficacy of bupropion and NRT David, Strong, et al, 2007;Johnstone et al, 2004;Lerman et al, 2003Lerman et al, , 2006Swan et al, 2005Swan et al, , 2007Yudkin et al, 2004). Given that SNPs associated with pharmacogenetic smoking cessation outcomes may manifest differing degrees of linkage disequilibrium (LD) depending on the population studied (e.g., ANKK1 rs1800497 and rs6277: D = 0.13 for Blacks; D = 0.74 for Whites; Gelernter et al, 2006), haplotype analyses may be necessary to identify genetic variants that contribute to smoking cessation outcomes in populations of different continental origins.…”
Section: Introductionmentioning
confidence: 99%
“…Several biologically plausible candidate gene variants have been identified within this genomic region in genetic association studies of nicotine dependence and smoking cessation (Abrous et al, 2002;Breen et al, 1999;Jonsson et al, 1996;Jonsson et al, 1999;Katoh & Katoh;Noble, Blum, Ritchie, Montgomery, & Sheridan, 1991;Noble, Gottschalk, Fallon, Ritchie, & Wu, 1997;Yang et al, 2007Yang et al, , 2008. For example, functional genetic variants in the DRD2 gene (i.e., rs6277 "exon [S] [C957T]"); rs1799732 "promoter (ins/del)" and ANKK1 gene (i.e., rs1800497 "TaqIA") have been associated with efficacy of NRT and bupropion for smoking cessation David, Strong, et al, 2007;Johnstone et al, 2004;Lerman et al, 2003Lerman et al, , 2006Swan et al, 2005Swan et al, , 2007Yudkin et al, 2004). Of the genetic variants within this cluster, the TaqIA variant is the most widely studied for association with smoking behavior.…”
Section: Introductionmentioning
confidence: 99%